Nutrimental status in the cellular extract of petiole and leaves of genotypes of roselle - Flores-Bernal, Emilia F.; Sandoval-Villa, Manuel; Guzmán-Martínez, María; Espinosa-Rodríguez, Mariana; Vázquez-Villamar, Mirna; Sabino-López, Juan E. (Ecosistemas y Recursos Agropecuarios, 2021)
There are several nutritional diagnosis techniques in plants that allow corrective fertilization decisions to be made. But, as in other crops, in roselle (Hibiscus sabdariffa L.) the nutritional status is not checked. The aim was to study the nutritional status of eight roselle genotypes in flowering, by analyzing the petiole cell extract (ECP), SPAD readings and plant tissue in the laboratory, for the establishment of nutritional reference indices. Eight roselle genotypes were collected and sown in 12 L polyethylene bags filled with a mixture of tezontle and bush soil (1:1 v/v) in a completely randomized design with five replications. The plants were grown in a greenhouse covered with white 800 µm plastic with 70% light transmission. The plants were fertilized with 44N-30P-20K kg ha-1 and watered with running water. SPAD readings were determined in recently mature leaves and NO3-, K+, Ca2+ and Na+ were determined in the petiole cell extract with ionometers. The leaves were processed for chemical analysis of total nitrogen, poporos, potassium, calcium, magnesium, iron, copper, zinc, manganese and boron. There were significant differences in the ions for ECP, SPAD readings and nutritional concentration in leaves of the genotypes studied. The nutrient concentración of the specific ions in the petiole cell extract, SPAD readings and in plant tissue can be used as reference values to compare with subsequent studies on this crop.